Perceptions of victims and perpetrators in sexual assault: the influence of relationship history - Chong, Germaine Nim Sze (Nanyang Technological University, 2023)
Sexual assault is an extremely pervasive and harmful crime against women, and the way that it is perceived by individuals can greatly influence the kind of treatment that victims receive. Certain factors, such as the length of relationship history between the victim and perpetrator, can alter the way that one evaluates the situation. The present study investigates how relationship history affects attributions of victim and perpetrator blame, perceptions of consent, and willingness to believe the victim. 156 adult participants (109 females, 47 males) recruited from the community in Singapore each read four vignettes depicting sexual assault scenarios, with each scenario involving a different relationship dynamic between the female victim and male perpetrator (strangers, first date, dating, married). Participants gave ratings for their responsibility attributions of the victim and perpetrator, their perception of whether the victim consented, and how much they would believe the victim. When relationship history was longer, participants blamed the victim more and the perpetrator less. Additionally, a longer relationship history created the impression that the victim consented more, and made participants less willing to believe the victim. This study also had the novel finding that perceptions of the victim's consent partially mediated the influence of relationship history on attributions of responsibility to the victim. Given the complex nature of real-world sexual assault cases, further research is needed to validate this study's findings, especially in an Asian context.